G protein-coupled receptor kinases (GRKs) in tumorigenesis and cancer progression: GPCR regulators and signaling hubs. (February 2018) - Nogués, Laura; Palacios-García, Julia; Reglero, Clara; Rivas, Verónica; Neves, María; Ribas, Catalina; Penela, Petronila; Mayor, Federico
Abstract: Increasing evidences point to G protein-coupled receptor kinases (GRKs), a subfamily of protein kinase A/G/C-like kinases, as relevant players in cancer progression, in a cell-type and tumor-specific way. Alterations in the expression and/or activity of particular GRKs have been identified in several types of tumors, and demonstrated to modulate the proliferation, survival or invasive properties of tumor cells by acting as integrating signaling nodes. GRKs are able to regulate the functionality of both G protein-coupled receptors (GPCR) and growth factor receptors and to directly control cytosolic, cytoskeletal or nuclear signaling components of pathways relevant for these processes. Furthermore, many chemokines as well as angiogenic and inflammatory factors present in the tumor microenvironment act through GPCR and other GRK-modulated signaling modules. Changes in the dosage of certain GRKs in the tumor stroma can alter tumor angiogenesis and the homing of immune cells, thus putting forward these kinases as potentially relevant modulators of the carcinoma-fibroblast-endothelial-immune cell network fostering tumor development and dissemination. A better understanding of the alterations in different GRK isoforms taking place during cancer development and metastasis in specific tumors and cell types and of its impact in signaling pathways would help to design novel therapeutic strategies.